Saving truth from paradox - Field, Hartry H., 1946- (Oxford University Press, 2008)
This is an investigation into paradoxes of truth and related issues, with occasional forays into notions such as vagueness, the nature of validity, and the Gödel incompleteness theorems. Hartry Field presents a new approach to the paradoxes and provides a systematic and detailed account of the main competing approaches.